A review on sparse fast fourier transform applications in image processing - Hadhrami Ab Ghani; Mohamad Razwan Abdul Malek; Muhammad Fadzli Kamarul Azmi; Muhammad Jefri Muril; Azizul Azizan (Institute of Advanced Engineering and Science, 2020)
Fast Fourier Transform has long been established as an essential tool in signal processing. To address the computational issues while helping the analysis work for multi-dimensional signals in image processing, sparse Fast Fourier Transform model is reviewed here when applied in different applications such as lithography optimization, cancer detection, evolutionary arts and wasterwater treatment. As the demand for higher dimensional signals in various applications especially multimedia appplications, the need for sparse Fast Fourier Transform grows higher.